2012
DOI: 10.1523/jneurosci.1467-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor-Dependent Afterdepolarizations Are Curtailed by Carbonic Anhydrase 14: Regulation of a Short-Term Postsynaptic Potentiation

Abstract: In the hippocampus, extracellular carbonic anhydrase (Car) speeds the buffering of an activity-generated rise in extracellular pH that impacts H+-sensitive N-methyl-D-aspartate receptors (NMDARs). We studied the role of Car14 in this brain structure, where it is expressed solely on neurons. Current-clamp responses were recorded from CA1 pyramidal neurons in wild type (WT) vs. Car14 knock out (KO) mice 2 s. before (control) and after (test) a 10 pulse, 100 Hz afferent train. In both WT and KO, the half width (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…A recent large scale single-cell RNA-seq study in the visual cortex identified Car12 as a unique marker of Layer 6 cortical neuron subtype (Tasic et al, 2016), but apart from this, virtually nothing is known about the function of Car12 in the nervous system. However, other extracellular carbonic anhydrases (ECAs) such as Car4 and Car14 have been well-studied in the brain, where they have been shown to modulate neuronal activity by regulating extracellular pH (Makani and Chesler, 2007;Svichar et al, 2009;Makani et al, 2012). In the hippocampus, several studies have shown that ECAs regulate excitatory synaptic transmission via pH-mediated modulation of NMDA receptor activation (Chen and Chesler, 2015).…”
Section: Enzymesmentioning
confidence: 99%
“…A recent large scale single-cell RNA-seq study in the visual cortex identified Car12 as a unique marker of Layer 6 cortical neuron subtype (Tasic et al, 2016), but apart from this, virtually nothing is known about the function of Car12 in the nervous system. However, other extracellular carbonic anhydrases (ECAs) such as Car4 and Car14 have been well-studied in the brain, where they have been shown to modulate neuronal activity by regulating extracellular pH (Makani and Chesler, 2007;Svichar et al, 2009;Makani et al, 2012). In the hippocampus, several studies have shown that ECAs regulate excitatory synaptic transmission via pH-mediated modulation of NMDA receptor activation (Chen and Chesler, 2015).…”
Section: Enzymesmentioning
confidence: 99%
“…Mechanistic explorations should also study selective intracellular versus extracellular carbonic anhydrase inhibitors (e.g., Perez Velazquez ; Makani et al. ; Collier et al. ) in their effects on presynaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in pH could modify the efficiency of enzymes [22], receptors [5, 2326], ionic pumps [4, 27, 28], and ionic channels [2931]. Many pH-sensitive molecules are membrane-bound and involved in the regulation of cellular excitability.…”
Section: Discussionmentioning
confidence: 99%